2022
DOI: 10.3390/insects13040395
|View full text |Cite
|
Sign up to set email alerts
|

Natural Repellents as a Method of Preventing Ant Damage to Microirrigation Systems

Abstract: Ants are important because they damage agricultural equipment, including microirrigation systems. The aim of this research was to assess the efficiency of the incorporation of repellents in drip irrigation tubing as a method of protection against ant damage. Unlike previous studies, we tested a series of nontoxic compounds that are repellent to ants. First, we assessed their repellent effects on a local ant species via olfactometer trials. Then, the candidates showing the best results (cinnamon essential oil, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Cheng et al (2008) indicated that both the indigenous cinnamon leaf essential oil and trans-cinnamaldehyde had an excellent inhibitory effect in controlling S. invicta [51]. Moreover, the repellents of cinnamon essential oil and p-anisaldehyde showed high avoidance efficiency against six species of ants, including Cardiocondyla batesii, Plagiolepis pygmaea, P. schmitzii, Solenopsis sp., T. nigerrimum, and T. semilaeve, where the pipes of a subsurface drip irrigation (SDI) system containing the two selected compounds remained almost intact, with no damage being caused by the ants [3].…”
Section: Plant-derived Repellent Substances For Use Against Antsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cheng et al (2008) indicated that both the indigenous cinnamon leaf essential oil and trans-cinnamaldehyde had an excellent inhibitory effect in controlling S. invicta [51]. Moreover, the repellents of cinnamon essential oil and p-anisaldehyde showed high avoidance efficiency against six species of ants, including Cardiocondyla batesii, Plagiolepis pygmaea, P. schmitzii, Solenopsis sp., T. nigerrimum, and T. semilaeve, where the pipes of a subsurface drip irrigation (SDI) system containing the two selected compounds remained almost intact, with no damage being caused by the ants [3].…”
Section: Plant-derived Repellent Substances For Use Against Antsmentioning
confidence: 99%
“…In addition, ants and humans can come into conflict in green spaces (including parks, gardens, and tourist attractions) and they can seriously interfere with the public leisure and entertainment activities of people (especially children). Ants can also damage agricultural equipment [3]. In addition, the problem of fire ants, leafcutter ants, termites, and other insects is very serious in tropical areas, causing extensive damage to crops and reforestation [4].…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Several reports have demonstrated that EA and/or BA have excellent repellent activity against many different species of insects, such as fruit flies, 13,14 mosquitoes 11,[14][15][16] and ants. 17,18 Consequently, these two anthranilates are thought to have the potential to be used as environmentally friendly and safe insect repellents.…”
Section: Introductionmentioning
confidence: 99%
“…Butyl anthranilate (BA), which has a mild, sweet fruity floral aroma, is a nearly colorless or pale straw‐colored liquid that is often applied as a filler in perfumes, dyes and medicines 11,12 . Several reports have demonstrated that EA and/or BA have excellent repellent activity against many different species of insects, such as fruit flies, 13,14 mosquitoes 11,14–16 and ants 17,18 . Consequently, these two anthranilates are thought to have the potential to be used as environmentally friendly and safe insect repellents.…”
Section: Introductionmentioning
confidence: 99%